COMPARATIVE ANALYSIS OF INDOOR AND OUTDOOR EMPLOYEE BALANCE AT MUHAMMADIYAH UNIVERSITY OF MALANG - Anugrah, Rakha Rizky; Bayu Prastowo; Safun Rahmanto (Rena Cipta Mandiri, 2024)
Background: Balance disorders in indoor and outdoor employees have an impact on decreased work performance, fatigue in the body, and can cause work-related illnesses. Making work not optimal and having an impact on daily life becomes disrupted. Working environmental conditions such as wet floors, uneven ground, non-sloping ground contours, insufficient lighting, excessive light glare, weather, and work that is carried out at a fast pace with heavy loads can affect balance disorders which can cause employee falls. Objectives: The purpose of this study was to find out the difference in balance between indoor and outdoor employees at the University of Muhammadiyah Malang. Methods: This study used a quantitative research design with this type of observational research using the one leg balance test and the time up and go test. Results: This study obtained results with the normality test obtaining a p value (> 0.005) and the Spearman test static test obtaining a value of 0.800 p (> 0.05) and the Spearman test dynamic test obtaining a value of 0.777 p (> 0.05). Conclusion: In conclusion, there is no difference in balance between indoor and outdoor employees at the University of Muhammadiyah Malang.